2022
DOI: 10.1007/s10067-022-06063-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the burden of osteoarthritis in Latin America: a rapid evidence assessment

Abstract: This rapid evidence assessment (REA) was conducted to explore the burden of weight-bearing joint osteoarthritis in the developing countries of Latin America. REA methodology used a standardized search strategy to identify observational studies published from 2010 to 23 April 2020 that reported outcomes pertaining to the epidemiology and humanistic or economic burden of weight-bearing osteoarthritis. Relevant data from each included study were used to populate bespoke data extraction tables and qualitatively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
3
0
2
Order By: Relevance
“…This has been described previously. 10 The protocol was prospectively registered with PROSPERO, an international database of systematic reviews in health and social care, welfare, public health, education, crime, justice, and international development: https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=180225 . Searches were conducted on April 23, 2020, in MEDLINE ® via Ovid ® , Embase ® via Ovid ® , and PubMed, for publications dated from January 1, 2010, onwards.…”
Section: Methodsmentioning
confidence: 99%
“…This has been described previously. 10 The protocol was prospectively registered with PROSPERO, an international database of systematic reviews in health and social care, welfare, public health, education, crime, justice, and international development: https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=180225 . Searches were conducted on April 23, 2020, in MEDLINE ® via Ovid ® , Embase ® via Ovid ® , and PubMed, for publications dated from January 1, 2010, onwards.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of both knee and hip OA were found to have increased dramatically, 2.9-fold and 3.1-fold, respectively, over the past three decades in this region [3,4]. Another study used a rapid evidence assessment to examine the burden of OA in Latin America [5 ▪▪ ]. The authors concluded that those with knee OA in Mexico reported higher levels of functional disability and worse Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores compared to those in Argentina and Brazil, likely in part due to differences in healthcare systems and infrastructure between countries [5 ▪▪ ].…”
Section: Understudied Populationsmentioning
confidence: 99%
“…Another study used a rapid evidence assessment to examine the burden of OA in Latin America [5 ▪▪ ]. The authors concluded that those with knee OA in Mexico reported higher levels of functional disability and worse Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores compared to those in Argentina and Brazil, likely in part due to differences in healthcare systems and infrastructure between countries [5 ▪▪ ]. Analyses into the prevalence and disability associated with OA globally are the key first steps to understanding the depth and impact of the disease.…”
Section: Understudied Populationsmentioning
confidence: 99%
“…Los datos de poblaciones en América Latina con gonalgia han mostrado diferencias, siendo México el país con una mayor disfunción física y peores puntuaciones en el índice WOMAC. (14) Esto coincide con poblaciones europeas con gonartrosis quienes, al mostrar un dolor moderado, limitación de la movilidad y cuidado personal, presentan una repercusión negativa en su calidad de vida y estado psicológico. (15) El Time Up and Go (TUG) se utiliza comúnmente para valorar la limitación de las actividades de andar y trasladarse de cualquier persona, se utilizó originalmente para valorar el riesgo de caídas en adultos mayores; sin embargo, actualmente es útil para detectar cambios en el balance o movilidad general de los pacientes, independientemente del tipo de comorbilidad de la persona.…”
Section: Antecedentesunclassified